Cultural Competence in Pediatrics: Health Care Provider Knowledge, Awareness, and Skills - Dabney, Kirk (Int J Environ Res Public Health, 2015)
The purpose of this study was to assess the effects of a cultural competence training (CCT) program on pediatric health care providers’ self-reported ability to provide culturally competent care to a diverse pediatric patient population. This quantitative, nested ecologic level study design used a repeated measure in the form of pre-test and post-test data to assess percent change in providers’ cultural awareness, experience working or learning about different cultures, and preparedness and skills in working with different cultures before and after CCT. The study was conducted between 2011 and 2012 in a pediatric hospital and associated outpatient offices. The sample consisted of pediatric health care providers from various departments, mainly physicians and nurses (n = 69). Participants completed a pre-intervention cultural competence assessment and then were subjected to a cultural competence-training program, after which they completed the assessment a second time. The baseline and post-intervention data were collected in the form of Likert scales and transformed into a quintile or quartile scale as appropriate. Data were assessed using paired t-tests or Wilcoxon’s signed-rank tests. Providers indicated a 13% increase in knowledge (53.9% vs. 66.7%, t = 3.4, p = 0.001), 8.7% increase in awareness (46.7% vs. 55.4%, t = 3.0, p = 0.002), and 8% statistically marginal increase in skills (66.4% vs. 74.5%, z = 1.8, p = 0.06). Culturally competent training in a pediatric environment significantly enhances knowledge, awareness and to some extent skills in providing care to culturally diverse patient population.